Photoreceptor layer thickness in age-related macular degeneration: the Beijing Eye Study : clinical science - Jonas, Jost B.; Panda-Jonas, Songhomitra; Pan, Zhe; Wu, Xiaodong; Wang, Ya Xing (British journal of ophthalmology, 2025)
Purpose To assess the photoreceptor layer thickness and its associations with age-related macular degeneration (AMD). - Methods Participants of the population-based Beijing Eye Study without optic nerve or retinal diseases (except for early and intermediate AMD) were examined by optical coherence tomography of the macula. - Results The study cohort was composed of 2426 participants (mean age: 62.8±9.1 years; range: 50-93 years), with 200 and 393 individuals affected by early AMD and intermediate AMD, respectively. In multivariable analysis, thickness of Henle’s fibre layer, outer nuclear layer, external limiting membrane and myoid zone (HOEM) combined was not significantly associated with AMD prevalence (beta: 0.03; p=0.08) or AMD stage (beta: 0.04; p=0.06), after adjusting for younger age (beta: −0.09; p<0.001), shorter axial length (beta: −0.07; p<0.001), thicker ellipsoid zone (EZ) (beta: 0.19; p<0.001), thicker photoreceptor outer segment (POS) layer (beta: 0.12; p<0.001), thicker subfoveal choroid (beta: 0.11; p<0.001) and thinner retinal pigment epithelium/Bruch’s membrane (RPE/BM) layer (beta: −0.17; p<0.001). Thicker EZ correlated with lower AMD prevalence (beta: −0.04; p=0.03) and lower AMD stage (beta: −0.02; p=0.02), with adjustment for older age (beta: 0.05; p=0.03), longer axial length (beta: 0.06; p=0.001), thicker HOEM (beta: 0.19; p<0.001) and thinner RPE/BM (beta: −0.31; p<0.001). Including only normal eyes and eyes with early AMD, EZ thickness was not significantly correlated with AMD prevalence (beta: −0.02; p=0.49). Thicker POS correlated with lower AMD prevalence (beta: −0.06; p<0.001) after adjusting for younger age (beta: −0.10; p<0.001), thicker HOEM (beta: 0.08; p<0.001) and thinner RPE/BM layer (beta: −0.62; p<0.001). If only normal eyes and eyes with early AMD were included, POS thickness was not significantly related to AMD prevalence (beta: −0.03; p=0.09). - Conclusions Thickness of HOEM, EZ and POS was not significantly associated with the prevalence of early AMD.